Seasonal changes of the morpho-biological characteristics of black rockcod Notothenia coriiceps (Nototheniidae) in the Argentine Islands Archipelago region - Trokhymets, V.N.; Zinkovskyi, A.V. (Український антарктичний журнал, 2017)
Black rockcod Notothenia coriiceps (Nototheniidae) is one of the common fish species of the Argentine Islands Archipelago region, and it is very common in the Southern Ocean waters. So, objective of the original research was to study the seasonal changes of biological characteristics of N. coriiceps individuals. The material was collected during the XII Ukrainian Antarctic Expedition in 2007-2008 Широколоба нототенія Notothenia coriiceps (Nototheniidae) належить до фонових видів риб у районі архіпелагу Аргентинські острови та в цілому характеризується широким розповсюдженням у водах Південного океану. Тому метою оригінальної наукової роботи є дослідження сезонних змін біологічних показників в особин N. coriiceps. Матеріали дослідження було зібрано під час XII Української антарктичної експедиції 2007-2008 рр. Широколобая нототения Notothenia coriiceps (Nototheniidae) принадлежит к фоновым видам рыб в районе архипелага Аргентинские острова, а также – характеризируется широким распространением в водах Южного океана в целом. Поэтому целью оригинальной научной работы является изучение сезонных изменений биологических характеристик N. coriiceps. Материалы исследования были собраны во время XII Украинской антарктической экспедиции 2007-2008 гг.